2015
DOI: 10.18632/oncotarget.4858
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput kinome screen reveals serum/glucocorticoid-regulated kinase 1 as a therapeutic target for NF2-deficient meningiomas

Abstract: Meningiomas are the most common primary intracranial adult tumor. All Neurofibromatosis 2 (NF2)-associated meningiomas and ~60% of sporadic meningiomas show loss of NF2 tumor suppressor protein. There are no effective medical therapies for progressive and recurrent meningiomas. Our previous work demonstrated aberrant activation of mTORC1 signaling that led to ongoing clinical trials with rapamycin analogs for NF2 and sporadic meningioma patients. Here we performed a high-throughput kinome screen to identify ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…Moreover, the sensitivity of RMS cell lines to the cytotoxic drug doxorubicin was enhanced, which is in complete accordance with reports that show SGK1 supporting cell proliferation, stimulating their migration and counteracting apoptosis in diverse tumor cell types [16, 29], including colorectal carcinoma [11-13, 16, 45], hepatocellular carcinoma [17, 18], breast cancer [18-20], prostate cancer [21, 22], glioblastoma [23-25], non-small cell lung cancer [26], meningiomas [27] and medulloblastoma [28]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the sensitivity of RMS cell lines to the cytotoxic drug doxorubicin was enhanced, which is in complete accordance with reports that show SGK1 supporting cell proliferation, stimulating their migration and counteracting apoptosis in diverse tumor cell types [16, 29], including colorectal carcinoma [11-13, 16, 45], hepatocellular carcinoma [17, 18], breast cancer [18-20], prostate cancer [21, 22], glioblastoma [23-25], non-small cell lung cancer [26], meningiomas [27] and medulloblastoma [28]. …”
Section: Discussionsupporting
confidence: 91%
“…Mechanisms conferring tumor cell survival and therapy resistance include the serum & glucocorticoid inducible kinase SGK1, initially identified in mammary tumor cells [8-14], yet then found as being ubiquitously expressed with strong emphasis in skeletal muscle [15] and highly upregulated in different tumors such as colonic cancer [16], hepatocellular carcinoma [17, 18], breast cancer [18-20], prostate cancer [21, 22], glioblastoma [23-25], non-small cell lung cancer [26], meningiomas [27], and medulloblastoma [28]. Several studies demonstrate a pivotal role for SGK1 in cell survival, cell proliferation and migration of tumor cells [16, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Whether mTOR Ser 2481 is expressed in atypical meningiomas still remains to be verified. However, the higher efficacy of the dual mTORC1/mTORC2 inhibitors compared to rapamycin in blocking the proliferation of meningioma cells is strongly in favor of this hypothesis. Finally, this study still leaves unsolved whether p‐mTOR expression is maintained in recurrent meningiomas, and whether it could represent a therapeutic target also in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Roberta L. Beauchamp et al [41] reported that independent activation of SGK1 and PAK1 may be partly responsible for the mTORC1 activation in NF2-deficient meningioma cells, and the group I PAK inhibitor FRAX597 may be improper for treatment for higher concentrations needed. Treatment with specific inhibitors of growth signaling pathways (MEK/PI3K/mTOR) demonstrated that in normal diploid colon epithelial cells (HCEC-1CT), PAK1 expression is regulated by MEK, PI3K, and mTOR [42].…”
Section: Discussionmentioning
confidence: 99%